European Pentecostalism - Dyer, Anne E.; Kay, William K., 1945- (Global Pentecostal and Charismatic Studies, 2011)
Starting from small numbers before 1914, the Pentecostal and charismatic movement now comprises nearly one third of the whole of the global Christian population. Scholarly accounts of Pentecostal and charismatic congregations in various countries have been written but this book does something new. It provides an interconnected account of Pentecostalism in Europe, something never before been attempted because of the diversity of languages spoken across the continent. This book shows how Pentecostalism spread from the north of Europe and how it fared during two horrific wars and under communist dictatorships. In doing so it provides new theological, historical and sociological information about Pentecostal churches in eastern and southern Europe, about the Catholic Charismatic Movement and about the state of western groupings.